Macrophage Migration Inhibitory Factor Triggers Inflammatory Responses During Very Virulent Infectious Bursal Disease Virus Infection - Liu, Aijing; Li, Hui; Qi, Xiaole; Wang, Qi; Yang, Bo; Wu, Tiantian; Yan, Nana; Li, Yue; Pan, Qing; Gao, Yulong; Gao, Li; Liu, Changjun; et al. (Frontiers in Microbiology, 2019)
Infectious bursal disease (IBD) is one of the main threats to the poultry industry worldwide. In China, very virulent IBD virus (vvIBDV) is the main prevalent virus strain, causing inflammation, immunosuppression, and high mortality in young chickens. To determine whether this acute inflammation can trigger lesions or even death in chickens, it is important to study the mechanism of vvIBDV pathogenicity. Thus, in the current study, we investigated the inflammation response, bursal lesions, and mortality in chickens caused by vvIBDV at different time points post the infection. Results showed an upregulation of proinflammatory cytokines, including interleukin-1β and interleukin-18, and macrophage infiltration in bursa in response to vvIBDV infection. High-throughput proteomic sequencing based on isobaric tags for relative and absolute quantitation showed that chicken macrophage migration inhibitory factor (chMIF) was upregulated uniquely in primary B cells infected with vvIBDV, compared with infection by non-pathogenic attenuated IBDV. We confirmed that chMIF was upregulated by vvIBDV infection both in vivo and in vitro. Moreover, chMIF was extracellularly secreted by infected DT40 and primary B cells. Further experiments revealed that the secreted chMIF could induce migration of peripheral blood mononuclear cells and promote transcription of proinflammatory cytokines in chicken primary macrophages. Notably, these effects of chMIF could be reduced by using an MIF specific inhibitor. Thus, our study elucidates critical molecular determinants underlying vvIBDV-mediated initiation of acute inflammation, which might be pivotal to understand the mechanism of vvIBDV pathogenicity.